Contrasting land uses in Mediterranean agro-silvo-pastoral systems generated patchy diversity patterns of vascular plants and below-ground microorganisms. - Bagella, Simonetta; Filigheddu, Rossella; Caria, Maria Carmela; Girlanda, Mariangela; Roggero, Pier Paolo (Comptes rendus biologies, 2014)
The aims of this paper were (i) to define how contrasting land uses affected plant biodiversity in Mediterranean agro-silvo-pastoral-systems across a gradient of disturbance regimes: cork oak forests, secondary grasslands, hay crops, grass covered vineyards, tilled vineyards; (ii) to determine whether these patterns mirrored those of below-ground microorganisms and whether the components of γ-diversity followed a similar model. The disturbance regimes affected plant assemblage composition. Species richness decreased with increasing land use intensity, the Shannon index showed the highest values in grasslands and hay crops. Plant assemblage composition patterns mirrored those of Basidiomycota and Ascomycota. Richness in Basidiomycota, denitrifying bacteria and microbial biomass showed the same trend as that observed for vascular plant richness. The Shannon index pattern of below-ground microorganisms was different from that of plants. The plant γ-diversity component model weakly mirrored those of Ascomycota. Patchy diversity patterns suggest that the maintenance of contrasting land uses associated with different productions typical of agro-silvo-pastoral-systems can guarantee the conservation of biodiversity.
The following values have no corresponding Zotero field: publisher: Academie des sciences accession-num: 25433564
Keywords: Cork oak forests; Grass covered vineyards; Grazing; Hay crops; Secondary grasslands; Tilled vineyards

Variation in soil C and microbial functions across tree canopy projection and open grassland microenvironments - Lai, Roberto; Lagomarsino, Alessandra; Ledda, Luigi; Roggero, Pier Paolo (TURKISH JOURNAL OF AGRICULTURE AND FORESTRY, 2014)
Mixtures of grasslands and perennial woody crops or vineyards represent a major source of potential carbon storage or release. Understanding the spatial variability of soil properties in these ecosystems is important in determining soil constraints related to the management of soil resources. The aims of the study were 1) to explore the spatial variability associated to the trees for soil C storage and its components and reactivity; and 2) to assess the similarities between microenvironments in terms of microbial functional diversity. Eight microenvironments characterized by different long-term soil management practices and different positions with respect to woody plant canopy soil vertical projections were selected in a Mediterranean agropastoral system. Four management types were considered: pasture, hay crop, grass-covered vineyard, and tilled vineyard. Soil organic C, microbial biomass, and respiration were measured to assess C storage and dynamics, while functional diversity was determined by means of soil enzyme activities. The results showed that the microenvironmental variation of soil organic C and functional microbial diversity generated by the tree canopies in the wooded grassland can be very relevant for an accurate assessment of soil organic C content and its dynamics. The same was not applicable to vineyards, where the spatial variation of both soil organic C and functional diversity was negligible, independently of the soil management practices. These results suggest that in such systems the microscale spatial variability generated by the trees is worth of further investigation for improving our understanding of the long-term management effects on soil C dynamics.
Keywords: agroforestry systems; carbon mineralization; Enzyme activity; long-term management; Tree effect; vineyards

Effects of long-term management practices on grassland plant assemblages in Mediterranean cork oak silvo-pastoral systems - Bagella, Simonetta; Salis, Lorenzo; Marrosu, Gian Marco; Rossetti, Ivo; Fanni, Stefania; Caria, Maria Carmela; Roggero, Pier Paolo (PLANT ECOLOGY, 2013)
The assessment of the effects of long-term management practices is relevant in understanding the current patterns of plant assemblages in semi-natural ecosystems. We hypothesized that the variety of management practices across different farming systems under the same ecological conditions directly and indirectly shapes these patterns via the long-term changes induced in soil features. The aims of this paper were to evaluate the influence of two sets of variables describing long-term management practices and soil features on plant assemblages and their importance in the context of Mediterranean silvo-pastoral systems. The analysis of variance revealed that richness and grazing value were not affected at all by grazing livestock species and soil tillage frequency and that they both showed relatively high absolute values for the specific context under study. Trifolium subterraneum was a key species in contributing to grassland grazing value and habitat biodiversity. The Canonical Correspondence Analysis highlighted the influence of management practices and soil features on plant assemblage composition, which was significantly affected by grazing livestock species and stocking rate and by soil pH and K content. The Redundancy Analysis showed that soil pH and related features were in turn affected by stocking rate, supporting our hypothesis that management practices influenced plant assemblage composition directly and indirectly via their long-term effects on soil features. The results also highlighted that a systemic analytical perspective applied at a grazing system scale can be effective in addressing sustainable grassland management issues in Mediterranean silvo-pastoral systems.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: grazing systems; soil features; Stocking rate; Tillage; Trifolium subterraneum